Assessment of bioavailability of ethylthiadiazolylamide of acetylaminohexanoic acid by intragastric administration in rabbits - A. S. Malygin; N. S. Popov; M. A. Demidova; S. B. Marasanov (Фармакокинетика и Фармакодинамика, 2018)
Resume. Relevance. Ethylthiadiazolamide of acetylaminohexanoic acid is a new non-steroidal anti-inflammatory agent from derivative of 1, 3, 4-thiadiazole and acexamic acid. Purpose. Evaluation of the bioavailability of ethylthiadiazolamide of acetylaminohexanoic acid with single intragastric administration to rabbits. Materials and Methods. Pharmacokinetic studies were performed using 6 rabbits of the Chinchilla breed. The study was conducted using an open, randomized, cross-sectional scheme. Ethylthiadiazolamide of acetylaminohexanoic acid was administered intravenously at a dose of 1 mg/kg in a 0.33 % solution of dimexide or intragastrically at a dose of 1 mg/kg in 20 ml of 2 % starch mucus. Determination of analyte in blood plasma was carried out by HPLC-MS/MS method. Sample preparation was carried out by the method of blood plasma protein precipitation by acetonitrile. Chromatography was performed with an analytical column Agilent InfinityLab Poroshell 120 EC-C18 2.7 |±m 4.6 x100 mm. As a mobile phase, a mixture of acetonitrile and deionized water at the ratio 30:70 with adding 0.1 % formic acid in the isocratic mode. The identification was carried out by mass spectrometry according to MRM m/z 285.2 → m/z 130.2. Results and Discussion. The maximum content of ethylthiadiazolamide of acetylaminohexanoic acid in blood plasma was 806.8 ± 65.6 ng/ml at 1.345 ± 0.081 h after intragastric administration. The area under the pharmacokinetic curve AUC0→36 was 5 088.1 ± 442.1 ngхh/ml, and the ratio AUC36→∞/AUC0→36 - 2,96 ± 1,59 %. Bioavailability of ethylthiadiazolamide of acetylaminohexanoic acid with intragastric administration to rabbits at a dose of 1 mg/kg as an aqueous suspension averaged 37 %. Conclusion. It is necessary to improve biopharmaceutical properties of ethylthiadiazolamide of acetylaminohexanoic acid to increase bioavailability.